Faktor-faktor Pendukung Pencegahan Fraud pada Bank Perkreditan Rakyat - Prena, Gine Das; Kusmawan, Reynaldi Mulyana (Jurnal Ilmiah Akuntansi, 2020)
This study aims to determine whether the understanding of Risk Based Internal Audit, Whistleblowing System, anti-fraud awareness, and the application of the principles of Good Corporate Governance affect the prevention of fraud in Rural Credit Banks in Bali Province. This study uses primary data sources, using instruments in the form of questionnaires. The population used in this study were auditor internal and bord of directors from 134 Rural Credit Banks and the sample used was auditor internal from 57 Rural Credit Banks taken purposive sampling. The analytical method used is quantitative analysis that is multiple linear analysis using SPSS test equipment. t test results show that Risk BasedÂ  Internal Audit, Whistleblowing System, Anti-Fraud awareness, and the application of the principles of Good Corporate Governance each have a positive effect on Fraud prevention